Directed Nanoscale Self-Assembly of Molecular Wires Interconnecting Nodal Points Using Monte Carlo Simulations - Boscoboinik, Alejandro Miguel (2015)
The influence of directing agents in the self-assembly of molecular wires to produce two-dimensional electronic nanoarchitectures is studied here using a Monte Carlo approach to simulate the effect of arbitrarily locating nodal points on a surface, from which the growth of self-assembled molecular wires can be nucleated. This is compared to experimental results reported for the self-assembly of molecular wires when 1,4-phenylenediisocyanide (PDI) is adsorbed on Au(111). The latter results in the formation of (Au-PDI)n organometallic chains, which were shown to be conductive when linked between gold nanoparticles on an insulating substrate. The present study analyzes, by means of stochastic methods, the influence of variables that affect the growth and design of self-assembled conductive nanoarchitectures, such as the distance between nodes, coverage of the monomeric units that leads to the formation of the desired architectures, and the interaction between the monomeric units. This work proposes an approach and sets the stage for the production of complex 2D nanoarchitectures using a bottom-up strategy but including the use of current state-of-the-art top-down technology as an integral part of the self-assembly strategy.